Positive attitude towards business ethics and social responsibility for improving corporate image - Violeta Milenkovska; Julijana Petrovska; Aleksandra Stoilkovska (UTMS Journal of Economics, 2019)
The paper deals with the elements of business ethics and social responsibility, as important factors for improving the corporate image of the organizations, and thus achieving a competitive advantage on the market. The competitiveness and development of the organization in conditions of more and more emphasized globalization depends on the ability of managers to make socially responsible decisions and to satisfy the different demands of the interested parties (individuals and groups). Social responsibility is a modern concept of leadership and managing organizations and the business in general, in which organizations voluntarily involve stakeholders, and sets social and environmental standards. The paper focuses on modern business ethics, ethical principles and social responsibility that managers need to have, since they are most expected to act responsibly and ethically, and thus to contribute to the promotion of the social values that represent the recognizable identity and corporate image of organizations. Empirical research was conducted on 140 respondents, 40 of whom are managers and 100 are employed, in many organizations that have a top quality management and quality control standard. The research shows that employees and managers in business organizations have the necessary knowledge and positive attitudes regarding the concept of social responsibility.
Keywords: A13; M14; M21; 330; social responsibility; organization; ethics; business; corporate identity; management